2w + 2l = 98 (1)

l = 2w - 5 (2)

substitute for l in eqn (1)

2w + 2(2w-5) = 98

expand

2w + 4w - 10 = 98

simplify

6w = 108

w = 18

substitute in (2)

l = 36 - 5

l = 31

Check in (1)

36 + 62 = 98 - answer checks

w = 18, l = 31

2w + 2l = 98 (1)

l = 2w - 5 (2)

substitute for l in eqn (1)

2w + 2(2w-5) = 98

expand

2w + 4w - 10 = 98

simplify

6w = 108

w = 18

substitute in (2)

l = 36 - 5

l = 31

Check in (1)

36 + 62 = 98 - answer checks

w = 18, l = 31

Didn't find the answer you were looking for?